Smart cities and digital transformation : empowering communities, limitless innovation, sustainable development and the next generation. - Lytras, Miltiadis D; Housawi, Abdulrahman A.; Alsaywid, Basim S. (Emerald Publishing Limited, 2023)
Smart Cities and Digital Transformation offers a three-tiered approach to tomorrow's cities in terms of limitless innovation, sustainable development and empowering communities.